2013
DOI: 10.2169/internalmedicine.52.0095
|View full text |Cite
|
Sign up to set email alerts
|

Hard Metal Lung Disease Successfully Treated with Inhaled Corticosteroids

Abstract: We herein report a case of hard metal lung disease that was successfully treated with inhaled corticosteroids. A 46-year-old man was admitted to our hospital due to coughing and an abnormal shadow on a chest radiograph. He had worked as a hard metal tool sharpener for five years. Chest computed tomography scans showed centrilobular micronodules and areas of ground-glass opacity in the bilateral lung fields. Videoassociated lung biopsy specimens revealed bronchocentric interstitial pneumonia and cellular bronch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…44,51,[62][63][64][65] Currently, treatments are limited and no disease-specific therapy or diagnostic tool exists. There has been some success in treating HMLD with corticosteroids or immunosuppressive therapies, 66,67 typically resulting in moderate attenuation of breathing challenges and delayed onset of further symptoms (ie, fibrosis and fluid in the lungs), but in most cases, avoidance of further hard metal exposure is the recommended course of action.…”
Section: Risk Of Wc-co Exposure: Hard Metal Lung Disease (Hmld) Prognmentioning
confidence: 99%
“…44,51,[62][63][64][65] Currently, treatments are limited and no disease-specific therapy or diagnostic tool exists. There has been some success in treating HMLD with corticosteroids or immunosuppressive therapies, 66,67 typically resulting in moderate attenuation of breathing challenges and delayed onset of further symptoms (ie, fibrosis and fluid in the lungs), but in most cases, avoidance of further hard metal exposure is the recommended course of action.…”
Section: Risk Of Wc-co Exposure: Hard Metal Lung Disease (Hmld) Prognmentioning
confidence: 99%
“…Occupational exposure during production of hard metal is associated with several adverse health effects implicating cobalt as the causing agent. Those effects include rhinitis, sinusitis, bronchitis ( Balmes, 1987 ; Cugell et al , 1990 ), asthma ( Shirakawa et al , 1989 ; Kusaka et al , 1989 ; Nemery et al , 1990 ), dose-related decreased lung function over time ( Kusaka et al , 1986a ; Rehfisch et al , 2012 ), and hard metal lung disease (HMLD) ( Nemery et al , 1990 ; Ruokonen et al , 1996 ; Nureki et al , 2013 ; Nakamura et al , 2014 ). Allergic dermatitis ( Kusaka et al , 1989 ; Nakamura et al , 2014 ), caused both by direct contact and by skin exposure from deposited air particles ( Gimenez Camarasa, 1967 ; Dooms-Goossens et al , 1986 ) is reported.…”
Section: Introductionmentioning
confidence: 99%
“…Among the 18 patients, six cases, including our patient, were treated with corticosteroids (Yokota et al 1996;Enriquez et al 2007;Bezerra et al 2009;Kim et al 2013;Nakamura et al 2014), because the symptoms and/or radiological findings did not show improvement even after avoiding dust exposure before corticosteroid therapy. However, the detailed information of remaining 12 cases were unknown (Schwarz et al 1994;Dunlop et al 2005;Sakamoto et al 2008;Moreira et al 2010;Kaneko et al 2010;Sakai et al 2010;Nureki et al 2013;Mizutani et al 2016). On the other hand, Huang et al (2012) reported that proper prevention of dust exposure (change of workplace, proper wearing of mask, maintenance of better exhaust ventilation and air condition monitoring in the workplace) was effective in patients with HMLD.…”
Section: Discussionmentioning
confidence: 99%